Restvärmehantering på AB Sandvik Coromant - Arab, Antonia; Evertsson, Erica; Forsell, Lovisa; Halberg, Christine; Pakola, Marina; Reinholdsson, Lukas; Wållberg, Ida (2020)
Industries are facing challenges concerning both climate impact and work environment. AB Sandvik Coromant, a metalworking industry, is not an exception. Due to high temperature processes, the work environment for the employees reaches high temperatures. In this report, two possible solutions are investigated; installation of a cooling machine and insulation of the process ventilation. These two alternatives are compared through simulations of heat transfer and room temperature, together with a Life Cycle Assessment. The desired result is to lower the room temperature to the recommended level. At maximum load this study shows that both insulation and the installing of a cooling machine, separately, would be able to decrease the room temperature significantly and fulfill the requirements. It is confirmed that the environmental impact of insulation is remarkably lower than the one of the cooling machine. The final conclusion is therefore that insulation is the most suitable solution to the issues regarding both climate impact and working environment. Although if the chosen maximum temperature is considered too high, a cooling machine would be required as a complement to insulation, to reach even lower temperatures.